Karl Barth"s male-female order: A kingpin of dogmatic disparity - Dreyer, Yolanda (HTS teologiese studies, 2007)
Karl Barth’s gender perspective is often analysed with reference to his so-called “theoethics” or “creational theology”. This perspective perpetuates an asymmetry in gender relations that was prevalent in Biblical times, throughout Christianity and to some extent still is visible today. He based his view on the subordination of women on an exegesis of Genesis 1:27 as “intertext” of Ephesians 5:22-23. Barth’s asymmetrical gender perspective is a product of his embedment in Western Christian tradition which in turn, is rooted in early Christian patriarchal theology. The aim of this article is to focus on Barth’s ontological reframing of the traditional understanding of the Biblical notion of human beings as created in the “image of God”. The article consists of four sections: (a) Luther’s and Calvin’s gender perspectives; (b) the Enlightenment failure to achieve emancipation; (c) gender disparity in Reformed theology; and (d) a feminist alternative.